2021
DOI: 10.1136/bjsports-2020-103717
|View full text |Cite
|
Sign up to set email alerts
|

Methods, challenges and benefits of a health monitoring programme for Norwegian Olympic and Paralympic athletes: the road from London 2012 to Tokyo 2020

Abstract: ObjectiveTo describe the implementation of a health monitoring programme for Norwegian Paralympic and Olympic candidates over five consecutive Olympic and Paralympic Games cycles (London 2012, Sochi 2014, Rio de Janeiro 2016, PyeongChang 2018 and Tokyo 2020).MethodsAthletes were monitored for 12–18 months preparing for the games using a weekly online questionnaire (OSTRC-H2) with follow-up by physicians and physiotherapists, who provided clinical care and classified reported problems.ResultsBetween 2011 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 29 publications
1
35
1
Order By: Relevance
“…The mean response proportion was less than 50%, which was inferior to that reported in previous epidemiological studies in elite athletes (69–91%) [ 2 , 19 , 20 ], but closer to that in lower level athletes (50–60%) [ 21 , 22 ]. Possible explanations could be the athletes’ level (all levels vs. national and international levels in other studies [ 2 , 19 ]), the culture ( Latin in our and Barboza et al [ 21 ] studies vs. Nordic [ 2 , 19 , 20 ]), the few feedbacks to athletes [ 21 ], or the specificities of athletics as individual sports [ 2 , 23 ]. As previously reported [ 15 , 21 , 22 ], we observed a decrease in the response proportions throughout the follow-up period.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The mean response proportion was less than 50%, which was inferior to that reported in previous epidemiological studies in elite athletes (69–91%) [ 2 , 19 , 20 ], but closer to that in lower level athletes (50–60%) [ 21 , 22 ]. Possible explanations could be the athletes’ level (all levels vs. national and international levels in other studies [ 2 , 19 ]), the culture ( Latin in our and Barboza et al [ 21 ] studies vs. Nordic [ 2 , 19 , 20 ]), the few feedbacks to athletes [ 21 ], or the specificities of athletics as individual sports [ 2 , 23 ]. As previously reported [ 15 , 21 , 22 ], we observed a decrease in the response proportions throughout the follow-up period.…”
Section: Discussioncontrasting
confidence: 91%
“…Efforts should be made to reach a high level of response proportion. In addition to regular automatic reminders to athletes, other strategies should be developed, for instance, having one investigator monitoring the response proportion during the study and trying to enforce participation, educating end-users on the interest of monitoring the evolution of some characteristics of athletes over the time (e.g., training load, pain, fatigue), providing some visual feedbacks of these characteristics and evolutions, and providing scientific evidence of the improvement of health and/or performance by using this monitoring [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A response rate of 74% is similar to previous studies using the same method in the Norwegian Olympic and Paralympic team, with weekly response rates ranging from 58% to 88% 13. We found that the band and drill company had a higher response rate, which might be due to a more regular schedule without field exercises, but we have not conducted any follow-up of the different companies to explore possible differences in military culture and attitudes towards injuries and health.…”
Section: Discussionsupporting
confidence: 80%
“…The average injury prevalence reported by conscripts in the Norwegian Army (28%) was quite similar to that among Norwegian Olympic athletes (32%) 13. However, the proportion (10%) reporting a substantial injury at any given time (affecting performance and participation at least to a moderate degree) was lower among soldiers than Olympic athletes (15%).…”
Section: Discussionmentioning
confidence: 53%
“…Being anxious about the physical disadvantage, paralytic athletes were regarded to be susceptible to sports injury. However, from study of Clarsen et al, the incidence of sport injury seemed to be comparable between Winter Paralympic athletes and Winter Olympic athletes [ 2 ]. Among winter sports, alpine skiing, Nordic skiing, and sledge hockey were extensively regarded as the 3 most popular items in disabled athletes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%